2017
DOI: 10.1074/jbc.m117.785105
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the riboflavin-binding protein retbindin reduces flavin levels and leads to progressive and dose-dependent degeneration of rods and cones

Abstract: The interface between the neural retina and the retinal pigment epithelium (RPE) is critical for several processes, including visual pigment regeneration and retinal attachment to the RPE. One of its most important functions is the exchange of metabolites between the photoreceptors and RPE because photoreceptor cells have very high energy demands, largely satisfied by oxidative metabolism. The riboflavin (RF) cofactors, flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), are two key cofactors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Though many mutations are rod-specific, death of cones generally ensues (Wert et al, 2014). Many suggest that rods provide critical trophic components into the retinal environment that ensure cone survival (Kelley et al, 2017) and because rods are the major cellular component of the photoreceptor layer, they contribute essential infrastructure for the cones (Steinberg, 1994;Ripps, 2002). Nevertheless, RP has demonstrated that cone survival is contingent upon rod photoreceptor health.…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
“…Though many mutations are rod-specific, death of cones generally ensues (Wert et al, 2014). Many suggest that rods provide critical trophic components into the retinal environment that ensure cone survival (Kelley et al, 2017) and because rods are the major cellular component of the photoreceptor layer, they contribute essential infrastructure for the cones (Steinberg, 1994;Ripps, 2002). Nevertheless, RP has demonstrated that cone survival is contingent upon rod photoreceptor health.…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
“…3 Retbindin is secreted into the IPM and peripherally anchored to the plasma membrane via electrostatic forces, and we showed that mice lacking retbindin (Rtbdn −/− ) exhibit retinal degeneration as well as defects in rod and cone function. 2,4 Our previous studies using both degenerative models that lack rods but retain some cones and models in which GFP is knocked into cells that express retbindin have shown that retbindin expression is limited to rods. 2,4 Retbindin shares significant homology with the riboflavin binding domain of chicken oviduct riboflavin binding protein (RBP).…”
mentioning
confidence: 99%
“…2,4 Our previous studies using both degenerative models that lack rods but retain some cones and models in which GFP is knocked into cells that express retbindin have shown that retbindin expression is limited to rods. 2,4 Retbindin shares significant homology with the riboflavin binding domain of chicken oviduct riboflavin binding protein (RBP). 1,2 Subsequently, we determined that retbindin binds riboflavin in vitro 2 and that flavin levels were reduced in Rtbdn −/− mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore surprising that three of the metabolites that accumulate in AMD are electrons suppliers to the respiratory chain through such electron transfer flavoproteins. Interestingly, reduced levels of riboflavin cofactors are known to induce photoreceptor cell death in mice [20] and alteration of retinal autofluorescence of mitochondrial flavoproteins has been evidenced in patients with AMD [21]. Our results suggest that this mitochondrial flavoproteins dysfunctionality in AMD may be indirectly perceptible in the blood of patients through the accumulation of their substrates.…”
Section: Discussionmentioning
confidence: 63%